Pengaruh Karakteristik Komite Audit terhadap Ketepatan Waktu Pelaporan Keuangan Perusahaan - Mutmainah, Siti; Kurniawan, Khomsin Fajar (Jurnal Akuntansi dan Governance Andalas, 2020)
This study aims to examine the effect of audit committee’s characteristics consist of independency, expertise, size, meeting frequencies, authority, and gender audit committee on the timeliness of corporate financial reporting. Audit report lag is a proxy of the timeliness of corporate financial reporting. The samples in this study are manufacturing companies that listed on Indonesian Stock Exchange (IDX) on 2016-2018 consist of 252 observations. The result shows that audit committee’s independency and size have positive significant and audit committee meeting frequencies has negative significant on audit report lag. Meanwhile, audit committee’s expertise, authority, and gender have no significant influence on audit report lag. The results of this study indicate the need to improve the performance of the audit committee in order to improve the timeliness of financial reporting. In accordance with the mechanisms of good corporate governance, policymakers can regulate the attributes needed to improve the effectiveness of the audit committee, for example the expertise provisions, the proportion of women, or statements of the authority.